PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PROBLEM BASED LEARNING BERBANTUAN LEMBAR KERJA PESERTA DIDIK - Azizah Azizah; Heni Purwati; Ahmad Buchori; Purwanto (STKIP Subang, 2023)
This research is classroom action research which aims to determine improvementsin mathematics learning outcomes, through the application of the Problem BasedLearning (PBL) model assisted by Student Worksheets. This research was carriedout in accordance with the lesson study procedures which consist of 3 cycles. Eachcycle includes: 1) planning, 2) implementation, 3) reflection and follow-up. Thesubjects of this research were 32 students from class IX B of SMP Negeri 6Semarang in the even semester of the 2022/2023 academic year. The data analysistechnique used uses documentation and tests in the form of formative assessmentof learning by looking at the increase in students' formative assessment learningoutcomes from three cycles with a limit of 85% reaching a KKM score of 74. Theoriginal learning outcomes of class IX students at SMP Negeri 6 Semarang wereobtained. completion was 63% to 86% from 86% to 87% and 87% to 91%. Theresearch results show that there is an increase in learning outcomes with theProblem Based Learning model assisted by Student Worksheets